68Ga‐nitroimidazole PET/CT imaging of hypoxia in tuberculosis: A case series - Philippa L Bresser; Janet Reed; Mike M Sathekge; Mariza Vorster (Journal of Medical Radiation Sciences, 2022)
Abstract Tuberculosis (TB) lesions in humans have been proven to be severely hypoxic with hypoxia leading to latency and dormancy of disease. Dormant TB lesions become less susceptible to standard TB treatment regimens with varying responses to treatment but may have increased susceptibility to nitroimidazole drugs. This in turn implies that positron emission tomography / computed tomography (PET/CT) imaging with radiolabelled nitroimidazoles may identify patients who will benefit from treatment with antimicrobial agents that are active against anaerobic bacteria. This case series aims to highlight the hypoxic uptake and retention of a novel 68Ga‐labelled hypoxia‐seeking agent in TB lesions at different time points during anti‐TB therapy using PET/CT imaging. Patients with confirmed TB underwent whole‐body PET/CT after administration of a 68Ga‐nitroimidazole derivative at baseline and follow‐up. Images were analysed both qualitatively and semi‐quantitatively. Hypoxic uptake and change in uptake over time were analysed using lesion‐to‐muscle ratio (LMR) and lesion‐to‐blood ratio (LBR). 68Ga‐nitroimidazole avid lesions were demonstrated most frequently in the upper lobes of the lung. Low‐grade hypoxic uptake was visualised in areas of consolidation, cavitation, nodules and lymph nodes. From baseline to follow‐up imaging, the LMR increased with persistent hypoxic load despite morphologic improvement. This case series highlights the dynamic hypoxic microenvironment in TB lesions. From these initial data, it appears that 68Ga‐nitroimidazole is a promising candidate for monitoring hypoxic load in patients diagnosed with TB. Such imaging could identify patients who would benefit from individualised therapy targeting other mechanisms in the TB microenvironment with the intention to predict or improve treatment response.